Desenvolvimento de um sistema de controle semiautomático em uma máquina ensacadeira de argamassa utilizando a plataforma arduino. - Lima, Francisco Danrley de (Universidade Federal Rural do Semi-Árido, 2019)
The construction sector has been shown a developing market in recent years. With this growth, the production and commercialization of construction products has been gaining more and more power in the market, such as the production of industrialized mortar. Industrialized mortar consists of a mixture of sand, cement and some additives, processed in an industrial plant and made available to the consumer on a semi-ready basis, requiring only mixing with water for use. The search for improvements in product quality and production processes will always be present in the industrial sector. On this way, this work was developed with the objective of partially automating a bagging machine, used in a construction products factory on a industrialized mortar production plant. The main components used for the prototype development was an Arduino Uno controller board and a bending load cell. The function of the system is to read the weight of the mortar package in real time, while it is being filled and, at the same time, to control the actuator responsible for filling using its weight as the main variable. The circuit was developed and installed in the equipment to perform practical tests. Through the tests, some problems inherent to the bagger structure were found. However, it was concluded that the developed circuit was able to read the load cell and control the motor responsible for the mortar bag filling process.
Monografia
Keywords: Argamassa industrializada; Ensacadeira; Automação; Arduino; ENGENHARIAS::ENGENHARIA MECANICA